Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855) - Carvalho, Marcelo R. De (Zootaxa, 2016)
A systematic revision of the rio Tocantins stingrays has confirmed the occurrence of a new species of Potamotrygon first discovered more than two decades ago but which lacked material for a thorough description. Field surveys since undertaken in the middle and upper rio Tocantins have assembled significant material that forms the basis of an ongoing revision of the diverse Tocantins potamotrygonid assemblage. Potamotrygon rex, sp. nov., is a very large, "black stingray" species from the mid and upper rio Tocantins that is closely related to P. henlei (Castelnau), which occurs in the lower Tocantins basin and in rio Araguaia; both species do not co-occur. Potamotrygon rex, sp. nov., has a unique blackish to dark brown dorsal color with numerous small, yellow to orange irregular spots usually forming distinct clusters on dorsal disc, with ocelli in center of clusters on posterior and outer disc, dorsal tail also with clusters but lateral tail with ocelli, and a dark brownish to gray color covering most of ventral surface except nasoral region, gill slits and anterior snout in some specimens, with small whitish spots on ventral disc, pelvic fins and tail. Potamotrygon rex, sp. nov., can be further distinguished by its broad pelvic-fin apices, lack of labial grooves, irregular double row of dorsal tail thorns, and in having two angular cartilages associated with each hyomandibula. Potamotrygon rex, sp. nov., P. henlei, P. leopoldi Castex & Castello, and another new Potamotrygon species from the rio Tapajós (in description) form a species-group (the "black stingrays") occurring in rivers draining the central Brazilian shield, characterized by their black to dark brown but highly ornate dorsal color, wide pelvic fins with broadly convex apices, among other features. Potamotrygon rex, sp. nov., is the 25th species of Potamotrygon, and highlights that very large new species of fishes still await discovery and description in the Neotropical region.